Psychological outcomes of familial ovarian cancer screening: No evidence of long-term harm - Brain, K; Lifford, K; Fraser, L; Rosenthal, A; Rogers, M; Lancastle, D; Phelps, C; Watson, E; Clements, A; Menon, U (2012)
Objectives: Ovarian cancer screening for women at increased genetic risk in the UK involves 4-monthly CA125 tests and annual ultrasound, with further tests prompted by an abnormal result. The study evaluated the longer-term psychological and behavioural effects of frequent ovarian screening. Methods: Women completed T1 questionnaires before their first routine 4-monthly CA125 test, and T2 follow-up questionnaires one week after their result. Women with abnormal results completed a further questionnaire one week after return to routine screening (T3 primary end-point). T4 questionnaires were sent at nine months. Measures included cancer distress, general anxiety/depression, reassurance, and withdrawal from screening. Results: A total 1999 (62%) of 3224 women completed T1 questionnaires. T2 questionnaires were completed by 1384/1609 participants (86%): 1217 (89%) with normal results and 167/242 (69%) with abnormal results. T3 questionnaires were completed by 141/163 (87%) women, with 912/1173 (78%) completing T4 questionnaires. Analysis of covariance indicated that, compared to women with normal results, women with abnormal results reported moderate cancer distress (F = 27.47, p ≤.001, η2 = 0.02) one week after their abnormal result and were significantly more likely to withdraw from screening (OR = 4.38, p ≤.001). These effects were not apparent at T3 or T4. The effect of screening result on general anxiety/depression or overall reassurance was not significant. Conclusions: Women participating in frequent ovarian screening who are recalled for an abnormal result may experience transient cancer-specific distress, which may prompt reconsideration of risk management options. Health professionals and policy makers may be reassured that frequent familial ovarian screening does not cause sustained psychological harm. © 2012 Elsevier Inc. All rights reserved.